Comparison of Sexual Self-Efficacy, 5-Hydroxyindoleacetic Acid Levels, and White Blood Cell Counts in Women with Orgasmic Disorder and Healthy Controls - Zarghami, Ilnaz; Mohammadi, Masoud (Health Nexus, 2024)
The present study aimed to compare sexual self-efficacy, 5-hydroxyindoleacetic acid levels, and white blood cell (WBC) counts in women with orgasmic disorder versus healthy controls. The research method was causal-comparative, and the population included all women diagnosed with orgasmic disorder in Shiraz during 2018. A convenience sampling method was used; thus, based on the research objectives, samples were taken from 35 women with orgasmic disorder and 35 women without such disorder, matched by age and educational level. WBC levels were measured using a complete blood count (CBC) test, and 5-hydroxyindoleacetic acid levels were determined by colorimetric methods and high-performance liquid chromatography (HPLC). Questionnaires were analyzed using SPSS version 20 software through descriptive and inferential statistics. The data were examined using the t-test. Results showed that there were significant differences in sexual self-efficacy between women with orgasmic disorder and healthy controls, with the former group exhibiting lower sexual self-efficacy. There were also significant differences in 5-hydroxyindoleacetic acid levels between the two groups, with higher levels observed in women with orgasmic disorder. However, no significant differences were found in WBC counts between the two groups.